ضمانات الحماية المدنية للمستهلك في التعاقد الالكتروني - باهي, التركي; محمود, حياة (مجلة البحوث في الحقوق والعلوم السياسية, 2021)
ما بين القوة والضعف وجدت الحرية التعاقدية التي كان القانون هو المنقذ لها وهو ما تجسد في الاختيار الحر للمستهلك في العقد الالكتروني الذي تولد نتيجة تطور وسائل الاتصال عبر شبـــكة الانترنت، حيث تغـــيرت أنمـــاط الممــــارسات التجارية وأصبـحت عـقود الاستهــــلاك تتم عــــبر تقنيـــات الكترونية كالهاتــــف الفاكس البـــريد الالكتروني، ومواقع الويب بهدف الحصول على القبول من إيجاب تـلقاه المستهلك عبر إعلانات إلكترونية، و أمام هذا التطور أولت التـشريعات الوطنية والدولية الحديثة اهتماما بالغا بعقد الاســـتهلاك الالكتروني حيث عجزت النظرية العامة للعقد عن حمايــــته مما أدى إلى ظــهور منظومة تشريعية وقائية هدفها تجسيد هــذه الحماية في عقود الاستهلاك في البـيئة الالكترونية. Between strength and weakness, there is contractual freedom, so that the law is its savior and which is embodied in the free choice of the consumer in the electronic contract that was giving birth result by the development of means of communication over the Internet, where the patterns of commercial practices changed and consumption contracts became carried out through electronic technologies such as telephone, fax, e-mail, and web sites via broadcast Free, aiming to gain acceptance from an affidavit received by the consumer via electronic advertisements Faced with this development, national and international modern legislations have paid great attention to the electronic consumption contract, as the general theory of the contract failed to protect it, which led to the emergence of a preventive legislative system aimed at embodying this protection in consumption contracts in the electronic environment

جرائم الغش التجاري الواقعة على المستهلك - لوالي, خالد; معاشي, أسماء (Ibn Khaldun University of Tiaret, 2021)
يعتبر الغش التجاري من أبرز الظواهر السلبية وأكثرها انتشارا في المجتمع، ولا يكاد يخلوأي تشريع من تجريم هذه الظاهرة، التي أصابت المستهلك في مأكله ومشربه وملبسه وأغلب متطلبات حياته الضرورية منها والكمالية، ومع تقدم أساليب الإنتاج والتصنيع تطورت أساليب ووسائل الغش والتحايل على المستهلكين من قبل المتدخلين في العملية الاستهلاكية. والمشرع الجزائري على غرار التشريعات المقارنة رصد جملة من القوانين وعلى رأسها قانون العقوبات وقانون حماية المستهلك وقمع الغش لحماية المستهلك حماية موضوعية من خلال تجريمه للخداع والغش و كذا حيازة مواد مغشوشة دون مبرر شرعي، وحماية إجرائية تتمثل في استحداث هيئات رقابية منها ما هي مركزية ومنها ما هي محلية لقمع الغش التجاري، كما خول المشرع الجزائري للقضاء صلاحية متابعة جرائم الغش التجاري وفق إجراءات خاصة بدءا بتحريك الدعوى العمومية مرورا بمحاضر الشرطة القضائية ومحاضر الجهات المكلفة بحماية المستهلك، انتهاء بمرحلتي التحقيق والحكم. Commercial fraud is one of the most important and prevalent negative phenomena in society, and hardly any legislation is exempt from criminalizing this phenomenon, which has plagued consumers in their food, drink, clothing and clothing. most of the necessary and luxury needs of his life. in the process of consumption. The Algerian legislator, like the comparative legislation, controls a certain number of laws, foremost among which the Penal Code, the Law on the protection of the consumer, and the repression of the fraud to protect the consumer objectively by criminalizing the deception and fraud, as well as possession of fraudulent products. materials without legal justification, and procedural protection represented in the creation of control bodies, some of which are central and others It is local to suppress commercial fraud The Algerian legislator has also empowered the judiciary to prosecute fraud offenses commercial according to special procedures, starting with the opening of the public case, passing through the records of the judicial police and the archives of the bodies responsible for consumer protection, ending with the phases of investigation and judgment
Keywords: Droit de la consommation